Genome-wide identification and expression analysis of sucrose phosphate synthase and sucrose-6-phosphate phosphatase family genes in Camellia sinensis - Shicai Liang; Huan Wang; Hiroto Yamashita; Shuning Zhang; Xuxu Lang; Jiaxuan Yue; Shan He; Yu Wang; Kai Fan; Zhaotang Ding; Takashi Ikka; Wenjun Qian (Beverage Plant Research)
Sucrose phosphate synthetase (SPS, EC 2.4.1.14) and sucrose phosphate phosphatase (SPP, EC 3.1.3.24) are two key enzymes for sucrose biosynthesis, which play essential roles in growth, development and stress responses of plants. However, the roles of SPS and SPP have not been illustrated well in tea plants until now. In this study, a unique CsSPP and five CsSPSs (CsSPS1-5) were identified from the tea plant genome. Bioinformatic analysis results found that CsSPP and CsSPSs were clustered together with the known SPPs and SPSs of other species, respectively, and their amino acid sequences contain the conserved domains required for sucrose biosynthesis. Tissue-specific analysis results showed that CsSPP and CsSPSs were widely involved in vegetative and reproductive growth of tea plant, among which the transcription levels of CsSPP was highest in immature stem, while CsSPSs were highest in flower. Spatio-temporal expression analysis results showed that all of these genes are involved in abiotic stress responses of tea plants. Meanwhile, SPS activity and the contents of sucrose, glucose, fructose, and total soluble sugar in 'Shuchazao' cultivar increased more than that of 'Baiye1' under low temperature conditions. Correlation analysis results showed that the expression profiles of CsSPS2/4/5 were significantly and positively correlated with sucrose content in 'Shuchazao' cultivars under low temperature conditions, suggesting the significant roles of these genes in sucrose accumulation. In conclusion, this study will provide a theoretical basis for further functional research of SPS and SPP in plants.